PENERAPAN MODEL TEBAK KATA DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN 1 TELAGAWARU TAHUN PEAJARAN 2016/2017 - Dedy Suprianto; Moh. Irawan Zain; Nurhasanah Nurhasannah; Mansur Hakim (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2020)
This research is motivated by the low student learning, it can be seen from the results of the midterm fifth grade students at SDN 1 Telagawaru 2016 ditegolong quite low. The purpose of this research is is to improve learning outcomes IPS students of class V SDN 1 Telagawaru through the implementation of a model of charades with audio-visual media in the academic year 2016/2017. This research is a classroom action research conducted in two cycles. Each cycle consists of planning, action, observation and evaluation and reflection. The method used to collect data in this research is to carry out observation and tests. In the first cycle activity score of students amounted to 34 are categorized quite active, which means that this category has not met the indicators and activities of teachers 9 categories both meaning has met the indicator, then the second cycle category for the activity of students classified as being active by obtaining a score of 42 and the activities of teachers is quite good with a score of 11, while for the evaluation of learning outcomes IPS seen from the classical completeness in which the first cycle value classical completeness of 72.09% with the number of students who completed the 31 of the 43 students who took the tests, the evaluation of the second cycle of classical completeness 83.72% by the number of students who completed is 36 students of 43, is in compliance with the indicators to be achieved. Thus, it can be concluded that the model of charades with audio-visual media to improve learning outcomes IPS students of class V SDN 1 Telagawau in the academic year 2016/2017.